Evaluation of anxious behavior in larval zebrafish (Danio rerio) after early life chronic stress exposure (2023)
Zebrafish (Danio rerio) have emerged as one of the most widely used animal models, particularly for neurobiological and genetic high throughput studies. The aim of this study was to evaluate larval zebrafish responses to chronic stressors by using behavioral assays in an effort to characterize early life anxiogenic behavior, which might influence development of neuropsychiatric disorders later on. After establishing a chronic unknown early life stress (CUELS) protocol which did not affect survival rates, notable stress- related behaviors were identified for stressed larvae. These included significant freezing, erratic behaviors and preference for lighter environments, all of which were not identifiable before the protocol. In the future, these results will build into valuable insights in the context of post traumatic stress disorder (PTSD), since standardizing methods for efficient identification of anxious patterns during the first weeks of development is crucial considering the fact that distressing stimuli leading to development of this and other disorders could be presented during this time.